Tugas Dan Wewenang Kepolisian Republik Indonesia Dalam Penanganan Kasus Narkoba Di Wilayah Provinsi Lampung - Dita Rizqita Sari; Abdul Rohim; Suta Ramadan (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Drug abuse is a serious problem that threatens the security and welfare of people around the world, including in Indonesia. The Bandar Lampung region, being one of the major cities in Lampung Province, is not immune to the negative impact of drug trafficking. The importance of handling drug cases has become a central issue in the context of national security and social welfare. To overcome this problem, the role and authority of the police as law enforcers is crucial. The method used in this research is qualitative method with descriptive analysis. This research aims to find out about the duties and authority of the police in facing drug challenges. The result of this research is that police synergy efforts between various law enforcement agencies and the government, such as those in the Bandar Lampung area, can provide many benefits and help improve the effectiveness of drug handling.